Digitalisasi Peradilan Perdata dalam Perspektif Access to Justice: Analisis Normatif terhadap Efektivitas dan Tantangan Implementasi E-Court di Indonesia - Siska Anugrah; Tasya Nadia Putri; Novandri Andesa; Mia Yulianti (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The digital transformation of the Indonesian judiciary through the e-Court system presents significant normative questions, particularly regarding the coherence of electronic evidence rules within existing civil procedural law. This article examines two primary issues: (1) the legal standing of electronic documents as evidence in civil proceedings conducted via e-Court under HIR (Herzien Inlandsch Reglement), RBg (Rechtsreglement voor de Buitengewesten), the Electronic Information and Transactions Law and relevant Supreme Court Regulations; and (2) the regulatory consistency of e-Court in realizing the principles of simple, expeditious and affordable justice as mandated by Article 4(2) of the Judicial Power Law. Employing a normative juridical method through statutory, conceptual and comparative approaches, this study reveals that electronic documents in e-Court occupy an ambivalent normative positionprocedurally recognized yet lacking equivalent evidentiary weight to authentic deeds under the classical HIR/RBg framework. Furthermore, an incongruence exists between the ideals of efficiency and accessibility embedded in e-Court and the structural reality of digital infrastructure disparities across Indonesian regions. This article contributes a normative reconstruction framework that aligns e-Court regulation with the substantive not merely procedural dimensions of access to justice.